OC-56 Adjusting problems to extrauterine life in newborns delivered by caesarean section. (6th June 2017) - Lupu, Vasile Valeriu; Burlea, Marin; Ignat, Ancuta
Abstract : The transition from intrauterine to extrauterine life is a complex physiological adaptation. The most common adjustment problems are present in preterm and in term infants delivered by caesarean section. Caesarean section performed at the request of the mother (in the absence of maternal or fetal indications) increase the risk of prolonged hospitalisation, can cause breathing problems in children and increases the risk of complications in a subsequent pregnancy. Also, breast feeding is delayed in children born by caesarean section. Birth by caesarean benefits are for short term: fewer surgical complications, low risk of bleeding, and absence of urinary incontinence. There are authors who claim that birth by caesarean section performed at the request of the mother, as well as emergency caesarean delivery is associated with a high morbidity risk to both mother and fetus.